Making Progress : Programmatic and Administrative Approaches for Multimodal Curricular Transformation - Bearden, Logan (Book collections on Project MUSE., 2022)
"An empirical investigation into the strategies and processes first-year composition programs can use to center multimodal work in their curricula. Presenting a series of flexible strategies, evolving considerations, and best practices that can be taken up, adapted, and implemented to achieve "multimodal curricular transformation," at their own institutions"--